9-Ethyl-3-(imidazo[1,2-a]pyrimidin-3-yl)-9H-carbazole - Huang, Ping-Hsin (International Union of Crystallography, 2008)
The title compound, C(20)H(16)N(4), is a precursor for the production of electron-transporting and -emitting materials. The bond lengths and angles in this compound are normal. In the crystal structure, there are no significant hydrogen-bonding interactions or π–π stacking interactions between molecules.